Curcumin Sensitizes Hepatocellular Carcinoma Cells to Radiation via Suppression of Radiation-Induced NF-κB Activity. (11th October 2015) - Hsu, Fei-Ting; Liu, Yu-Chang; Liu, Tsu-Te; Hwang, Jeng-Jong
Abstract : The effects and possible underlying mechanism of curcumin combined with radiation in human hepatocellular carcinoma (HCC) cells in vitro were evaluated. The effects of curcumin, radiation, and combination of both on cell viability, apoptosis, NF- κ B activation, and expressions of NF- κ B downstream effector proteins were investigated with 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), NF- κ B reporter gene, mitochondrial membrane potential (MMP), electrophoretic mobility shift (EMSA), and Western blot assays in Huh7-NF- κ B- luc2, Hep3B, and HepG2 cells. Effect of I kappa B alpha mutant (I κ B α M) vector, a specific inhibitor of NF- κ B activation, on radiation-induced loss of MMP was also evaluated. Results show that curcumin not only significantly enhances radiation-induced cytotoxicity and depletion of MMP but inhibits radiation-induced NF- κ B activity and expressions of NF- κ B downstream proteins in HCC cells. I κ B α M vector also shows similar effects. In conclusion, we suggest that curcumin augments anticancer effects of radiation via the suppression of NF- κ B activation.